2005
DOI: 10.1002/em.20116
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of genotoxicity and the carcinogenic mode of action forortho-phenylphenol

Abstract: Ortho-phenylphenol (OPP) and its sodium salt (SOPP) are commercial products that have wide human exposure and have been shown in several studies to be rodent carcinogens. Genetic toxicology data were assessed in an attempt to understand the carcinogenic mode of action of OPP and SOPP. More than 130 studies were evaluated to determine if OPP, SOPP, or any of their enzymatic or nonenzymatic breakdown products react directly with DNA to induce mutation, changes in chromosome structure or number, DNA repair, or no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 63 publications
0
23
0
Order By: Relevance
“…OPP and its hepatic metabolite PHQ can produce urinary bladder hyperplasia and tumors (Hiraga and Fujii, 1984) but do not cause DNA damage or gene mutations and are therefore typical of non-genotoxic carcinogens (Brusick, 2005). Many chemicals considered carcinogenic are categorized as non-genotoxic carcinogens (Duesberg and Rasnick, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…OPP and its hepatic metabolite PHQ can produce urinary bladder hyperplasia and tumors (Hiraga and Fujii, 1984) but do not cause DNA damage or gene mutations and are therefore typical of non-genotoxic carcinogens (Brusick, 2005). Many chemicals considered carcinogenic are categorized as non-genotoxic carcinogens (Duesberg and Rasnick, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…PHQ does not generate γ-H2AX foci Previously, it was reported that PHQ neither binds nor cleaves DNA in vitro and in vivo (Brusick, 2005;Reitz et al, 1983). Moreover, some reports suggested that PHQ causes DNA damage (Tayama and Nakagawa, 1994;Nakagawa and Tayama, 1996;Murata et al, 1999).…”
Section: Phq Induces Apoptosismentioning
confidence: 97%
See 3 more Smart Citations